THE SIO2-H2O SYSTEM ALONG THE LOWER THREE-PHASE CURVE AND APPROXIMATE VALUES OF CRITICAL END-POINT TEMPERATURE - Aksyuk A.M. (My University, 1997)
The review and recalculation of all experimental data on the solubility of quartz and amorphous silica in liquid water and saturated vapour along the lower three-phase curve up to the critical end-points give the relation: in MSiO2(1 or v) = -[a1 + a2 In (MH2O(1)/MH2O(V)) + 1/(a3 In (MH2O(1)/MH2O(V)) + a4)] (± σ), where MSiO2 is a molar concentration (mol/dm3) of SiO2 (1 or v) in liquid water or vapour, respectively; (MH2O(1)/MH2O(V)) is a ratio of molar concentrations of H2O in liquid water and vapour, respectively. Constants: a1, a2, a3, a4 and standard deviation (± σ) are (1) for solubility of quartz in liquid water: 0.8958, 0.7081, 0.1283, 0.1217 and ± 0.218; (2) for solubility of quartz in vapour: 0.055, 3.8851, 0.1283, 0.1217 and ± 0.286; (3) for solubility of amorphous silica in liquid water: 0.4565, 0.4083, 0.0474, 0.2911 and ± 0.117; (4) for solubility of amorphous silica in vapour: -0.3843, 3.5853, 0.0474, 0.2911 and ± 0. 185, respectively. Distribution of silica between liquid water and saturated vapour fits the equation: In (MSiO2(1)/MSiO2(v)) = 3.177 In (MH2O(1)/MH2O(V)) - 0.8408 (± 0.068). The equations result from all the experimental data on silica solubility along the lower three-phase curve within the accuracy of the experimental measurements and provide evidence that the SiO2-H2O system must have a critical end-point temperature lower than that of pure water. The values of the critical temperature are in the interval 646.384-647.071 K (Tc of H2O is 647.096 K). The simple model of silica distribution, with Kd = (MSiO2(1)/MSiO2(v))/[MH2O(1)/M H2O(v))]n=const is valid along a three-phase line from 500 K to 646.23 K. The hydration number n of silica in liquid water and vapour is equal to 3.177 H2O molecules on average. The equation: In (MH2O(1)/MH2O(v)) + 1/[exp (0.1011 + 0.08182 In θ + 0.009746 (In θ)2.078) - 1], where θ = T/(T - 647.096), can be used for quick calculations since it has a maximum deviation measured from Wagner & Pruss's (1993) data that is less than 0.01 for the temperature (T) interval 338.15-647.096 K).